Supercritical fluid extraction of Lavandula stoechas L. ssp cariensis (Boiss.) Rozeira - Akgün, NA; Akgün, M; Dinçer, S; Akgerman, A (ALLURED PUBL CORP, 2001)
The flowers of Lavandula stoechas L, ssp. cariensis (Boiss.) Rozeira were extracted in both a batch and semicontinuous system by supercritical COB. In the first stage, experiments were performed in a batch system based on response surface methodology (RSM). Parameters used were pressure, temperature, mixing speed and extraction time, and were coded as, X-1, X-2, X-3 and X-4, respectively. These parameters were investigated at three levels (-1, 0 and 1). The dependent variable, Y, was taken as the volatile concentrate yield of supercritical fluid extraction. It was calculated with respect to the yield of solvent extraction by dichloromethane. In the second stage, experiments were carried out in a semi-continuous system at constant pressure and temperature, and different CO2 flow rates. Concentrations of volatile components were determined as a function of extraction time and CO2 residence time.
Keywords: Lavandula stoechas ssp cariensis; Labiatae; supercritical CO2 extraction; response surface methodology; CARBON-DIOXIDE; ESSENTIAL OILS; CO2 EXTRACTION; SEED; Chemistry; Food Science & Technology